Effectiveness of mixed tea plant extract gel with chitosan on fibroblast cells after tooth extraction of Wistar rats - Anggayanti, Nyoman Ayu; Sudirman, Putu Lestari; Sari, Ni Nyoman Rian Permata; Suryani, I Gusti Ayu Putu Diah (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: Tooth extraction can cause the damage of hard and soft tissue. When an injury occurs, fibroblast will respond in the wound healing process. Herbal medicines such as green tea and chitosan can be used in wound healing. The polyphenol content in green tea, namely EGCG, has an anti-inflammatory effect, increasing wound healing. In wound healing, chitosan promotes hemostasis and tissue recovery. Based on several previous studies, the use of 1.2% green tea extract was effective for improving wound healing in rat open wound models, chitosan 1% could trigger the proliferation of fibroblasts in the wound healing process after tooth extraction. The aim of this study is to analyze the effect of gel mixture of extract Camellia sinensis 1,2% with chitosan 1% on post-tooth extraction wound of Wistar rats. Methods: This was a randomized post-test only control group design using 40 Wistar rats which were randomly divided into 2 groups. Each group underwent intramuscular anesthesia on the rat's thigh and tooth extraction of mandibular left incisor. The treatment group was applied mixed gel of extract Camellia sinensis 1.2% and 1% chitosan as much as 0.01 ml and the control group was not given any treatment, after that decapitated on days 1, 3, 5, and 7. Result: The mean number of treated fibroblasts was higher than the control group on days 1, 3, 5, 7, respectively, 75.00; 176.00; 349.00 and 427.00 cells. The mean difference in the number of fibroblasts was significant with p-value 0.001 (p>0.05). Conclusions:  Mixed extract gel of Camellia sinensis and chitosan increased fibroblasts in wound healing process after tooth extraction of Wistar rats with the highest mean of fibroblast on the 7th day.Keywords: mixed tea leaves,chitosan, fibroblast,wound healing